Socio- economic factors that impinge computer usage in administration works among village leaders in Malaysia - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Abu Hassan, Musa; Alby, Jeffrey Lawrence D'Silva (Academic Journals, 2010)
The main purpose of this paper is to discover and determine the socio-economic factors that impinge the usage of computer in the administration work among village leaders in Malaysia. Using simple random sampling, a total of 240 village leaders which are the Village Development and Security Committee members, have been selected as the respondents for this study. Face to face interview was conducted to gain the data needed. To run the appropriate analyses, SPSS software was employed. Based on the results gained, the level of computer usage in administration work among Village Development and Security Committee members was at a moderate level. There were significant difference in computer usage in administration work in the factors of gender, ICT courses attended, type of position, education and zone where the Village Development and Security Committee members live. Results show that there was significant and positive relationship between usage of computer in administration work and income per month. Positive and significant relationship also was detected between computer usage in administration work and knowledge on computer usage while significant and negative relationship can be identified between computer usage in administration work and age. To enhance computer usage in administration work among Village Development and Security Committee members, it is recommended that every Village Development and Security Committee office and member should be supplied with at least a computer and internet connection. Furthermore, subsidy on purchasing computer should be provided to Village Development and Security Committee members. Special training courses can be introduced to Village Development and Security Committee members in order to inform them on the benefits of using the computer.